The bungalow – part of India's vernacular heritage. Issue 4 (3rd July 2016) - Bhardwaj, Monalisa; Garg, Pushplata
Abstract : Further to the entry of the East India Company, British people became resident in the Indian sub-continent down to 1947 and even later. Their distinct socio-cultural traditions and practices in an environment which was different from Britain resulted in a distinctive indigenous-like response towards building. Their built environment was acutely sensitive to the locally available resources and adapted to their in-transit lifestyle; and it sustained their social, economic and cultural environment. Their buildings are part of the heritage of South Asia and South East Asia.